2023
DOI: 10.3389/fpubh.2023.1153136
|View full text |Cite
|
Sign up to set email alerts
|

A multinational cross-sectional study on the awareness and concerns of healthcare providers toward monkeypox and the promotion of the monkeypox vaccination

Abstract: BackgroundThe aim of this study was to explore potential healthcare workers' (HCWs) concerns about the monkeypox virus in order to create practical solutions to manage this disease.MethodsOnline cross-sectional research was conducted in 11 Arabic countries (Egypt, Saudi Arabia, Yemen, Syria, Libya, Algeria, Tunisia, Iraq, Palestine, Jordan, and Sudan) from 2 August 2022 to 28 December 2022.ResultsApproximately 82% of respondents felt the need to acquire further information. The acceptability of the vaccine aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Forty-nine articles were eligible for full-text screening. From these, 30 studies [ 1 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] were included in the meta-analysis. The PRISMA flow diagram of the study is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-nine articles were eligible for full-text screening. From these, 30 studies [ 1 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] were included in the meta-analysis. The PRISMA flow diagram of the study is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…According to NOS, six [ 13 , 18 , 24 , 25 , 27 , 37 ] of the included studies were of high quality, twenty-one [ 1 , 12 , 14 , 15 , 16 , 17 , 19 , 20 , 21 , 22 , 26 , 28 , 29 , 30 , 31 , 32 , 34 , 36 , 38 , 39 , 40 ] of moderate quality, and three [ 23 , 33 , 35 ] of low quality ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The present study assessed the knowledge, attitudes, and perceptions of HCWs and medical students regarding Mpox. To our knowledge, few national reports have assessed the knowledge and attitude of Mpox in this specific group ( Abd ElHafeez et al., 2023 ; Alkalash et al., 2023 ; Swed et al., 2023a ; Swed et al., 2023b ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Roess, et al [ 28 ] indicated that the findings imply that the existing program of film-based educational activities helps enhance knowledge concerning disease-specific issues and may motivate people to seek out medical advice when mpox is detected. Moreover, Swed, et al [ 29 ] demonstrated that medical students and healthcare workers in the Arab world are more concerned with the COVID−19 virus than the mpox virus. Most medical practitioners have a basic understanding of the mpox virus.…”
Section: Discussionmentioning
confidence: 99%